NOTCH signaling in COVID-19: a central hub controlling genes, proteins, and cells that mediate SARS-CoV-2 entry, the inflammatory response, and lung regeneration - Baindara, Piyush; Sarker, Md Bodruzzaman; Earhart, Alexander P.; Mandal, Santi M.; Schrum, Adam G. (Frontiers in Cellular and Infection Microbiology, 2022)
In the lungs of infected individuals, the downstream molecular signaling pathways induced by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) are incompletely understood. Here, we describe and examine predictions of a model in which NOTCH may represent a central signaling axis in lung infection in Coronavirus Disease 2019 (COVID-19). A pathway involving NOTCH signaling, furin, ADAM17, and ACE2 may be capable of increasing SARS-CoV-2 viral entry and infection. NOTCH signaling can also upregulate IL-6 and pro-inflammatory mediators induced to hyperactivation in COVID-19. Furthermore, if NOTCH signaling fails to turn down properly and stays elevated, airway regeneration during lung healing can be inhibited, a process that may be at play in COVID-19. With specific NOTCH inhibitor drugs in development and clinical trials for other diseases, the roles of NOTCH in all of these processes central to both infection and healing merit contemplation if such drugs might be applied to COVID-19 patients.